2022
DOI: 10.5603/pjnns.a2021.0054
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic year in a sample of Polish myasthenia gravis patients: an observational study

Abstract: Aim of the study: Coronavirus disease 2019 (COVID-19) incidence, mortality, recovery and hospitalisation rates vary in different countries. This study aimed to present the clinical characteristics of a sample of unvaccinated Polish myasthenia gravis (MG) patients during the first year of the COVID-19 pandemic, taking into account the number of MG exacerbations, a detailed description of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection course, and the need to modify immunosuppressive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The burden of COVID-19 in MG patients over the last two years has been the object of a few case series and retrospective studies [ 4 , 33 , 34 ], demonstrating a clinical deterioration of MG patients and going as far as admission to the ICU in more severe cases [ 11 , 35 , 36 , 37 , 38 ]. These studies reported up to 30% lethality [ 4 , 33 , 36 , 37 , 39 ] and a high rate of complications [ 33 , 34 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of COVID-19 in MG patients over the last two years has been the object of a few case series and retrospective studies [ 4 , 33 , 34 ], demonstrating a clinical deterioration of MG patients and going as far as admission to the ICU in more severe cases [ 11 , 35 , 36 , 37 , 38 ]. These studies reported up to 30% lethality [ 4 , 33 , 36 , 37 , 39 ] and a high rate of complications [ 33 , 34 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The burden of COVID-19 in MG patients over the last two years has been the object of a few case series and retrospective studies [ 4 , 33 , 34 ], demonstrating a clinical deterioration of MG patients and going as far as admission to the ICU in more severe cases [ 11 , 35 , 36 , 37 , 38 ]. These studies reported up to 30% lethality [ 4 , 33 , 36 , 37 , 39 ] and a high rate of complications [ 33 , 34 , 36 , 37 , 38 ]. The prevalence of COVID-19 is broadly variable between population studies, from between 0.96 to 30%, with data heterogeneity reflecting several factors—including diffusion of SARS-CoV2, the period of study, and vaccination policies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These figures are valuable because of analyzing a number of patients, but they did not consider international variations in the infection course. Unexpectedly, studies in the French and Polish cohorts showed COVID-19 had limited effect on most MG patients, while high myasthenia gravis foundation of America (MGFA) class (≥IV) before COVID-19 was associated with severe COVID-19 (117,120). IST did not have a significant impact on infection risk (120,121).…”
Section: Risk-benefit Assessment and Should Mg Patients Be Vaccinated?mentioning
confidence: 93%
“…IST did not have a significant impact on infection risk (120,121). Another important aspect influencing the infection course in MG patients is international differences in the number of vaccinated populations as those who get vaccinated will form a "cocoon effect" to protect those who cannot be vaccinated (117).…”
Section: Risk-benefit Assessment and Should Mg Patients Be Vaccinated?mentioning
confidence: 96%
See 1 more Smart Citation